Perceived Brand Equity in Professional Sports Teams: A Zimbabwean Consumers’Perspective - Charumbira, Lysias Tapiwanashe (Asian Business Review, 2015)
The study explored the antecedents, dimensions and market consequences of the brand perceptions held by Zimbabwean consumers for professional football teams and developed a strategic brand management framework that can bridge existing practical and theoretical knowledge gaps in the management of sports brands in the country. The study was grounded on the exploratory sequential mixed methods research design. In the qualitative strand of the study, data was collected by means of such qualitative data collection procedures as, free-thought listing, semi-structured interviews and focus group discussions. The findings from the qualitative phase were used to generate data collection instruments for questionnaire survey and assess the overall prevalence of the variables that were identified in the first phase from a large number of users of football brands. The NVivo 10 and SPSS version 21.0 software packages were used to analyze qualitative and quantitative data, respectively. The study identified and classified the antecedents of brand perceptions held by Zimbabwean consumers for professional sports teams into consumption experience-trigged antecedents, significant others-triggered antecedents and sports entity-triggered antecedents. The results show that fan loyalty trends for local professional football teams function in tandem with the ethnic identity systems in the country. However, the globalization of football has led to the dilution of national particularities in the game. The findings support the conceptualization of perceived brand equity in as an aggregate of brand awareness and brand associations. Zimbabwean consumers of football brands perceived European professional football teams as the market leaders in their brand category .South African professional football teams were ranked second and Zimbabwean professional football teams were positioned at the bottom of the brand leadership rankings in the minds of Zimbabwean consumers of football brands. The study illustrated how the brand the perceptions held by Zimbabwean corporate and individual consumers for professional football teams have generated negative and positive market consequences.